Resolução de problemas de geometria métrica espacial com utilização da tecnologia da informação e comunicação - BIZINOTO, José Henrique (2016)
This research has the goal of o ering an activity to second year high school pupils, aiming at teaching some Space Metric Geometry, and more speci cally, at calculating areas and volumes of geometric solids such as cones , cylinders, spheres, pyramids and prisms, with the aid of technologies, with the GeoGebra software. In order to perform the activity, some trends in Maths teaching were approached, with emphasis mainly on Problem Resolution and on Information technology and Communication.